2021
DOI: 10.1055/s-0040-1722329
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Dual Medication Therapy (Oral Acetaminophen and Oral Ibuprofen) for the Management of Patent Ductus Arteriosus in Extremely Premature Infants: A Feasibility Trial

Abstract: Objective The study aimed to evaluate the efficacy of dual medication therapy (DMT) with oral acetaminophen and oral ibuprofen for the closure of a hemodynamically significant patent ductus arteriosus (hsPDA). Study Design In a prospective case–control cohort study (July 2017–May 2019), infants <29 weeks' gestational age and birth weight <1,000 g at ≤14 postnatal days with hsPDA and ratio of the smallest ductal diameter to the ostium of the left pulmonary artery diameter >0.5 were eligible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 39 publications
1
24
0
Order By: Relevance
“…Nine studies were considered to be relevant after initial screening. As described in the PRISMA ow diagram, three studies were excluded, leaving six (4 NRS [13,23,25,26] and 2 RCTs [22,24]) for inclusion in this systematic review. (Figure 1) We found one ongoing trial in a clinical trials registry (Clinical Trials # NCT03648437).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Nine studies were considered to be relevant after initial screening. As described in the PRISMA ow diagram, three studies were excluded, leaving six (4 NRS [13,23,25,26] and 2 RCTs [22,24]) for inclusion in this systematic review. (Figure 1) We found one ongoing trial in a clinical trials registry (Clinical Trials # NCT03648437).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Four studies [22,23,24,26] reported no differences in liver function tests pre-and post-treatment with acetaminophen. Only two studies [13,23] reported acetaminophen levels; the mean/median value of acetaminophen level on day 3 of medication administration was less than 25 mcg/ml.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Current RCTs, like the Baby-OSCAR trial [ 35 ], management of the PDA trial (NCT03456336), and the BeNeDuctus trial [ 36 ], will hopefully add to the available knowledge and will guide our way either to more aggressive treatment with monotherapy (ibuprofen or paracetamol) or even combined therapy (ibuprofen and paracetamol) or to a more expectant approach [ 37 , 38 ]. Furthermore, advances in percutaneous ductal closure might lead to reconsideration of early invasive closure for a select group of patients [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…We read the article written by Shah et al with interest and would like to share our opinion on it. 1 In the study in which the synchronous use of ibuprofen and paracetamol treatment was recommended in the article, successful closure rate was observed with dual therapy in 20 infants. In the discussion part of the article, its use was recommended due to the success of a highly effective treatment with combined therapy.…”
mentioning
confidence: 99%